2007
DOI: 10.1103/physrevb.76.045303
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensionally confined optical modes in quantum-well microtube ring resonators

Abstract: We report on microtube ring resonators with quantum wells embedded as an optically active material. Optical modes are observed over a broad energy range. Their properties strongly depend on the exact geometry of the microtube along its axis. In particular, we observe ͑i͒ preferential emission of light on the inside edge of the microtube and ͑ii͒ confinement of light also in the direction of the tube axis by an axially varying geometry, which is explained in an expanded waveguide model.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 12 publications
1
39
1
Order By: Relevance
“…At the interface between liquid and air we record a spectrum that is a combination of the previous ones ͓black spectrum in Fig. 2͑a͔͒; this is evidence that the observed mode shift is not caused by any geometrical factors due to structural inhomogeneities of the tube wall, 19 i.e., we illuminate a specific portion of microtube and we collect both air mode and solution mode in a single shot of light.…”
Section: On-chip Si/ Sio X Microtube Refractometermentioning
confidence: 96%
See 1 more Smart Citation
“…At the interface between liquid and air we record a spectrum that is a combination of the previous ones ͓black spectrum in Fig. 2͑a͔͒; this is evidence that the observed mode shift is not caused by any geometrical factors due to structural inhomogeneities of the tube wall, 19 i.e., we illuminate a specific portion of microtube and we collect both air mode and solution mode in a single shot of light.…”
Section: On-chip Si/ Sio X Microtube Refractometermentioning
confidence: 96%
“…These plots are performed after substracting the broad background emission. 19 From the integrated PL intensity map shown in Figs. 2͑c͒ and 2͑d͒, it is possible to reveal spatial regions with two distinctive spectral fingerprints.…”
Section: On-chip Si/ Sio X Microtube Refractometermentioning
confidence: 99%
“…It has been reported that the details of the tube geometry including the edge smoothness, intentionally created bottlelike notches, and periodic undulations have led to directional emission or better light confinement. [11][12][13] The demonstration of patterned rolled-up tubes provides new device prospects that involve spatial periodicity. For example, with proper design, the holes can be lined up after rolling for curved photonic crystal structures.…”
mentioning
confidence: 99%
“…[6][7][8] We have studied rolled-up tubes using membranes not only with patterns at the edges but also throughout the entire membranes. Shown in Figure 3 are tubes formed from patterned membrane with periodic arrays of holes.…”
Section: Patterned Rolled-up Tubesmentioning
confidence: 99%